La non-réciprocité d’un tiers induit la méfiance chez les singes capucins - James R Anderson; Benoit Bucher; Margaux Levasseur; Kazuo Fujita (Revue de Primatologie)
Recent studies have established that some species of primates are able to detect reciprocity and non-reciprocity in the context of exchanges of objects between third parties. For example, we have shown that capuchin monkeys discriminate between a human actor who exchanges equitably with a third party and an actor who does not respect reciprocity of exchange. More specifically, monkeys were significantly less willing to accept food from the non-reciprocator. In other words, the monkeys took a binary decision to engage preferentially with one actor at the expense of the other. In a new study, we asked whether monkeys would differentially trust two actors depending on the degree of reciprocity shown by the latter. Following a fair or an unfair exchange, one of the two actors started to transfer pieces of food to within reach of the monkey. In this situation of delay of gratification, the monkey can start to eat the food whenever it desires, but doing so stops the transfer; thus to maximize the amount of food obtained the monkey should wait and let the number of food items accumulate. Results showed that the monkeys were less likely to show delay of gratification when the food was transferred by an actor who behaved non-reciprocally in the exchange with a third party. This tendency towards “impulsive” responding was especially evident when the total quantity of food potentially available was unknown to the monkey, in other words, in a situation of uncertainty. We conclude from these data that non-reciprocity in a third-party exchange can induce a reaction of distrust in capuchin monkeys.